PERANCANGAN SISTEM INFORMASI POINT OF SALES (POS) BERBASIS WEB (STUDI KASUS : MINIMARKET SMJ PAAL 11) - AHADI, AHMAD HUSNA; -, Gustina (FORTECH (Journal of Information Technology), 2023)
Minimarket SMJ Paal 11, which is one of the retail business players, has a desire to utilize web technology to improve operational efficiency, especially in recording stocks and transactions. Currently, Minimarket SMJ Paal 11 still uses manual recording for stocks and transactions. Given the growing and increasing number of customers, there is a need for an information system that can support the recording of stocks and transactions efficiently. This is expected to increase efficiency and provide satisfaction to customers, because the entire transaction process can be completed more quickly. This study aims to design a web-based Point Of Sales (POS) Information System with the hope of optimizing the process of recording stock and transactions at SMJ Paal 11Minimarket. The method used in this design is the waterfall method with PHP programming language, Apache webserver, and MySQL database as a database for storing data. This information system is run locallyhosted and can be accessed by several devices in one network, ensuring ease of access and use. With the presence of web technology in this system, it is expected that SMJ Paal 11Minimarket can keep up with industry developments, improve recording accuracy, and provide more responsive services to customers.